2018
DOI: 10.1002/mrm.27556
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of PD, T1, T2, T2*, and ∆B0 using magnetic resonance fingerprinting with background gradient compensation

Abstract: Purpose This study aims to estimate PD, T1, T2, T2*, and normalΔB0 simultaneously using magnetic resonance fingerprinting (MRF) with compensation of the linearly varying background field. Methods MRF based on fast imaging with steady‐state precession (FISP) and multi‐echo spoiled gradient (SPGR) schemes are alternatively used, which encode T2 and T2*, respectively. Simulations are performed to determine the appropriate ratio of the FISP and SPGR sections with respect to the T2 and T2* accuracy. Additionally, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…29 Pkpk field inhomogeneity values of 1.6 ppm in the brain, 4.8 ppm in the breast, 5.6 ppm in the liver, and 4.8 ppm in the spinal cord were reported with active shimming. 27,[30][31][32] Hence, there are four objectives that will be addressed herein. First, we will relate MRI quality recommendations for RT to B 0 field homogeneity for systems designed for diagnostic MRI, RT simulation, and MR-IGRT.…”
Section: B B 0 Field Homogeneity and Mri Qualitymentioning
confidence: 99%
“…29 Pkpk field inhomogeneity values of 1.6 ppm in the brain, 4.8 ppm in the breast, 5.6 ppm in the liver, and 4.8 ppm in the spinal cord were reported with active shimming. 27,[30][31][32] Hence, there are four objectives that will be addressed herein. First, we will relate MRI quality recommendations for RT to B 0 field homogeneity for systems designed for diagnostic MRI, RT simulation, and MR-IGRT.…”
Section: B B 0 Field Homogeneity and Mri Qualitymentioning
confidence: 99%
“…This leads to faster dictionary generation, lower storage requirements and faster dictionary matching. For example as a rough comparison, in our case, the dictionary size is over three orders of magnitude smaller than a previously reported study (16) that used spirals to estimate the same tissue relaxation parameters (T1, T2, T2*).…”
Section: ) Discussionmentioning
confidence: 78%
“…Wyatt et al explored a variable-echo-time (TE) scheme to incorporate T2* sensitivity into the originally proposed MRF pulse sequence (15). Hong et al did so by combining a fast imaging with steady-state precession (FISP) sequence (sensitive to T2) and a multi-echo spoiled gradient echo (SPGR) sequence (sensitive to T2*) (16). Lastly, Wang et al used a quadratic-RF phase increment pattern to create T2* sensitivity (17).…”
mentioning
confidence: 99%
“…In a breast MRF study using MRF-FISP, 37 a dictionary with 20,059 columns representing possible T 1 , T 2 combinations was used, whereas in a brain tumor study using MRF-bSSFP, 72 the additional dimension of off-resonance increases the dictionary size to 287,709 columns. In the case where the sequence is also sensitized to quantify T 1 , T 2 , off-resonance, and T 2 *, the number of columns in the dictionary was reported to be over 30 million in Wang et al, 61 and 64 million in Hong et al 63 Inner product pattern matching has been shown to be accurate and robust to the high degree of aliasing artifacts due to undersampling in several of the initial MRF studies, including Ma et al 1 and Jiang et al 5 Also shown in both, 1,5 the number of timepoints used in the sequence will have a direct impact on the quality and accuracy of the T 1 and T 2 maps. Therefore, for the sequences in these initial studies, the number of timepoints was generally between 1000 to 3000.…”
Section: Reconstruction and Quantificationmentioning
confidence: 99%